2017
DOI: 10.1007/s10554-017-1098-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between interleukin-6 and the risk of cardiac events measured by coronary computed tomography angiography

Abstract: Interleukin-6 (IL-6) has been found to be a predictor of heart attack. We aimed to investigate the relationship of risk factor IL-6 with extent and severity of the coronary artery disease (CAD) evaluated using coronary computed tomography angiography (CCTA). A total of 303 participants without history of CAD undergoing CCTA were enrolled. Using the model of risk-adjusted Cox proportional-hazards, the association of IL-6 level with major adverse cardiac events (MACE) was detected. The participants were assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…This indicates that IL-6 is also a risk factor for subclinical or clinical atherosclerosis. Some previous cohort studies showed that patients with high levels of IL-6 had an increased atherosclerotic burden and higher risk of major adverse cardiac events compared with individuals with lower levels of IL-6 [24, 25]. Interestingly, Bacchiega et al found that the IL-6-blocking agent tocilizumab significantly reduced CRP concentrations, together with parameters of systemic inflammation [26].…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that IL-6 is also a risk factor for subclinical or clinical atherosclerosis. Some previous cohort studies showed that patients with high levels of IL-6 had an increased atherosclerotic burden and higher risk of major adverse cardiac events compared with individuals with lower levels of IL-6 [24, 25]. Interestingly, Bacchiega et al found that the IL-6-blocking agent tocilizumab significantly reduced CRP concentrations, together with parameters of systemic inflammation [26].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, luteolin is a polyphenolic compound from Danshen, which exerts cardiovascular protective effects for the roles of reducing oxidative stress, and inhibiting in ammation and apoptosis [37]. Tanshinone IIa is another compound existed in Danshen that can perform anti-ischemia, anti-arrhythmia, anti-atherosclerosis, and anti-coagulation [38]. The above active ingredients provided basis for the pharmacological activities of ZD acting on CHD.…”
Section: Discussionmentioning
confidence: 99%
“…Demographic data and hepatic events risk factors, such as gender, age, family history, smoking status, diabetes, dyslipidemia, body mass index (BMI), waist circumference, low-density lipoprotein (LDL), high-density lipoprotein (HDL), glucose, liver fat fraction, liver volume, visceral fat volume, and subcutaneous fat volume were acquired by a standardized questionnaire and clinical assay. Smoking status was classified into never, past, or current smoker (at least 6 months, at least one cigarette per day) (16). Diabetes was defined as hemoglobin A1c (HbA1c) higher than 6.5%.…”
Section: Methodsmentioning
confidence: 99%